(untitled) - Hosoya, Yūichi (Tokyo, 2019)
This work explores hotly debated security-related matters from a standard viewpoint on international politics and diplomatic history. It also advocates in a bold yet level-headed manner the form Japan’s security should take and the path Japan should follow to make that a reality.
Keywords: Nhật Bản,Japan; Chính trị và chính phủ,Politics and government